Impact of Cognitive Inhibition training on Mental Flexibility performance of Student with Learning Disability - Mohsen Rafikhah; Mohammad Mohajerani (Vesnu Publications, 2015)
Introduction: Executive functions, including inhibition and Flexibility are important for many of human behavior. Hence, emphasis has led to interventions to improved executive function. The aim of this study was examination of Impact of cognitive inhibition training on Flexibility performance of student with learning disability. Materials and Methods: The design of this study was a pretest-posttest with control group. The 30 students with learning disability were selected by means of convenience sampling (15 students in experimental group and 15 students in control group). The experimental group underwent a 10 session's cognitive inhibition training. All the participants were assessed through Wisconsin Card Sorting Test. The obtained data were statistically analyzed by MANCOVA using SPSS software (version 19, SPSS Inc., Chicago, IL). Result: Results showed a significant difference between experimental and control groups in Number of Categories (P= 0/001) also significant difference between experimental and control groups in Perseverative Errors (p= 0/05). Conclusion: According to these results, cognitive inhibition training have a positive effect on flexibility performance. Keywords: executive functions, cognitive inhibition, mental flexibility, learning disability